Pengaruh Financial Distress dan Audit Report Lag terhadap Integritas Laporan Keuangan dengan Komite Audit sebagai Pemoderasi - Muhamad Arthur Riandi; Suciati Muanifah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This research analyzes the effect of Financial Distress and Audit Report Lag on Financial Statement Integrity moderated by the Audit Committee. Financial Statement Integrity plays an important role as a foundation of trust that ensures financial information is presented honestly, accurately, and transparently to support decision making. The study was conducted on energy sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Twelve companies met the sample criteria in this study, with the sampling method using Purposive Sampling, resulting in a total sample of 60. The data analysis technique used Panel Data Regression with the help of the Eviews series 12 application. The results of the study state that Financial Distress and Audit Report Lag simultaneously affect Financial Statement Integrity, Financial Distress affects Financial Statement Integrity, Audit Report Lag does not affect Financial Statement Integrity, the Audit Committee is able to moderate the effect of Financial Distress on Financial Statement Integrity, and the Audit Committee is able to moderate the effect of Audit Report Lag on Financial Statement Integrity.